Pathways to psychopathology risk: neonatal limbic structures and the postnatal environment - Arya, Bhavya (Nanyang Technological University, 2024)
Children’s psychopathology risk presents a significant public health concern. Pathways to psychopathology risk may be conceptualized as interactions between biological and environmental factors across the prenatal, perinatal and postnatal periods. This study elucidates such interactions among a subsample of 93 triads drawing from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort. Specifically, we examined whether relations between prenatal maternal mental health and early childhood psychopathology risk (internalizing and externalizing behaviours measured when children were 4 years of age) were moderated by postnatal paternal mental health. Secondly, we examined whether relations between postnatal paternal mental health and early childhood psychopathology risk were moderated by neonatal limbic structures (hippocampus and amygdala volumes). While we found consistent associations between prenatal maternal mental health and children’s psychopathology risk, these relations were not moderated by postnatal paternal mental health. Yet, both neonatal left hippocampus and bilateral amygdala moderated associations between postnatal paternal mental health and children’s psychopathology risk, where the hippocampus appeared to be a marker of differential susceptibility (indicating a risk/resilience model) and the amygdala a marker of vantage sensitivity (indicating a resilience model). Results suggest that larger neonatal limbic structures may function as neonatal neurophenotypes underlying inter-individual differences in sensitivity to the environment which further shape psychopathology risk. Within this context, we discuss avenues for future research that may investigate other biological and environmental influences to further illuminate the complex pathways to psychopathology. Our findings may offer insights into the planning of targeted and well-timed interventions for children’s mental health.